2018
DOI: 10.4103/ortho.ijortho_555_17
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal Fractures — Should We or Should We not Operate?

Abstract: The best treatment for displaced, intraarticular fractures of the calcaneum remains controversial. Surgical treatment of these injuries is challenging and have a considerable learning curve. Studies comparing operative with nonoperative treatment including randomized trials and meta-analyses are fraught with a considerable number of confounders including highly variable fracture patterns, soft-tissue conditions, patient characteristics, surgeon experience, limited sensitivity of outcome measures, and rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 110 publications
0
33
1
4
Order By: Relevance
“…The AOFAS score was chosen even though it has not been validated because it is easy to use, is well established, and has been used in a previous study. 11 The results of the AOFAS score were interpreted as follows: 90-100 = excellent; 80-89 = good; 70-79 = fair; <70 = poor. No other evaluation/scoring system was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AOFAS score was chosen even though it has not been validated because it is easy to use, is well established, and has been used in a previous study. 11 The results of the AOFAS score were interpreted as follows: 90-100 = excellent; 80-89 = good; 70-79 = fair; <70 = poor. No other evaluation/scoring system was used.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review concluded that the majority of displaced, intra-articular fractures are best treated by open reduction and internal fixation, and that less invasive approaches with modern locking fixation have the potential to minimize soft tissue complications with anatomic reduction and stable fixation. 11 In a previous study, the accuracy and maintenance of reduction as well as complications and the ultimate function of patients treated with limited open reduction and internal fixation was validated against a group of patients treated with the extended lateral L-shaped approach. 23 For 24 months we followed a cohort of patients treated with this approach and fixation technique, which was unchanged for 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that have shown better outcomes with non-operative management 9 . Some authors have investigated operative management and got good results 10 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the term 'lovers fracture' is not used again as the circumstances leading to the terminology is not frequent. The decision to manage conservatively or not depends on the nature of the injury, the expertise of the surgeon, the availability of equipment, and the finance of the patient (13). Generally, conservative treatment is offered to those with minimal injury and non-displaced fractures which are extra-articular.…”
Section: Discussionmentioning
confidence: 99%